Analisis Kesulitan Siswa Dalam Pembelajaran Matematika Pokok Bahasan Operasi Hitung Bilangan Bulat kelas V SD Negeri 021 Bangkinang - Jusmainur Jusmainur; Zulhendri Zulhendri (Jurnal Pendidikan Tuntas, 2023)
The purpose of this study is to determine where the location of difficulty and factors that cause difficulties in learning mathematics on the subject of integer count operation. Research subjects are taken that is class V which has the average value of mathematics still under Minimum Exhaustiveness Criteria (KKM). Data collection methods used were test method, observation method, interview method. The test method is used to obtain student completion data on the counting integer counting material in the form of essay 10 items. Observation method is used to determine the condition of subjects during the learning activities of mathematics and to know the factors that can affect the learning process of mathematics. And interview method is done to know clearly problem faced by student when study material counting integer. From the data of final analysis result, the percentage of students difficulties in skill 50% including enough category, difficulties in understanding the concept of 23.3% including less category and difficulty in problem solving by 20% including less category. So expect teachers in shaping the pattern of teaching mathematics is not solely shown in the students' skills in solving the problem. But more important is how to invite students to understand and understand and master the existing concepts well and correctly, so that students do not have difficulty in learning mathematics.